Room temperature continuous wave operation of injection quantum dot microdisk lasers. (October 2015) - Kryzhanovskaya, N V; Maximov, M V; Nadtochiy, A M; Blokhin, S A; Bobrov, M A; Kulagina, M M; Troshkov, S I; Zadiranov, Yu M; Lipovskii, A A; Moiseev, E I; Kudashova, Yu V; Ustinov, V M; et al.
Abstract: We present results of characterization of injection microdisk lasers with InAs/InGaAs self-organized quantum dot active region grown on a GaAs substrate. The minimal microdisk diameter is 15 μm. The microlasers operate in continuous wave regime at room temperature without external cooling. Lasing wavelength is around 1.26... 1.27 μm, minimal threshold current is 1.6 mA (threshold current density 900 A/cm 2 ). Specific thermal impedance is estimated to be 5·0 -3 °C·cm 2 /W.